Metabolite changes during developmental transitions in Adonis amurensis Regel et Radde flowers: Insights from HPLC-MS analysis - Zun Xingzun; Wang Hongtao (PLoS ONE, 2025)
Adonis amurensis Regel et Radde is a remarkable and important spring ephemeral plant and gained considerable attention because of its remarkable medicinal properties. Extensive research has been conducted on its therapeutic applications, physical characteristics, flowering patterns, reproductive, cultural and molecular biology. However, there is a lack of comprehensive understanding regarding the metabolic changes associated with flower developmental stages. This study was designed to investigate the changes in metabolites and their interrelationships at five distinct developmental stages of A . amurensis flower: Flower Primordium (FP), Sepal Stage (SE), Perianth Primordium (PE), Stamens Stage (SE), and Pistil Stage (PI). High-performance liquid chromatography coupled with mass spectrometry (HPLC-MS) was utilized to investigate and characterize the metabolites associated with specific flower developmental stages. The various stages of flower development exerted a substantial influence on both the quantity and composition of metabolites present, signifying significant changes in the types and quantities of metabolites throughout the developmental progression of the flower. Metabolite Set Enrichment Analysis (MSEA) and annotation via the KEGG database highlighted enriched pathways such as flavonoid biosynthesis and plant hormone signal transduction, which are crucial for flower maturation. The highest number of differentially expressed metabolites was identified between the SE and PI stages, emphasizing a marked appreciation in metabolite expression linked to the development of reproductive organs. Key pathways such as flavonoid biosynthesis and plant hormone signal transduction were markedly enriched, underscoring their roles in flower maturation and potential pharmacological applications. Our research not only helps us in understanding the metabolomic dynamics during the flower development of A . amurensis but also emphasizes the potential pharmacological implication of stage-specific metabolites. Identifying these metabolites can help targeted bioprospecting and optimization of extraction methods to tackle the plant’s full therapeutic potential, particularly in the development of treatments for cardiac insufficiency, edema, and possibly cancer.